2000
DOI: 10.1046/j.1440-1754.2000.00446.x
|View full text |Cite
|
Sign up to set email alerts
|

Methylxanthines and sensorineural outcome at 14 years in children < 1501 g birthweight

Abstract: Theophylline therapy in the newborn period is associated with some evidence of harmful, but also helpful sensorineural effects at 14 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…We reasoned that if long-term harms were identified with the CAP trial, one mechanism that could potentially have been implicated was reduced cerebral blood flow. Given the long-term cohort study to 14 years of age of preterm infants treated with aminophylline showed an increase in the incidence of cerebral palsy (15), it remains to be determined that the CAP trial benefits persist to 5 years corrected age (21). Given the long-term cohort study to 14 years of age of preterm infants treated with aminophylline showed an increase in the incidence of cerebral palsy (15), it remains to be determined that the CAP trial benefits persist to 5 years corrected age (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We reasoned that if long-term harms were identified with the CAP trial, one mechanism that could potentially have been implicated was reduced cerebral blood flow. Given the long-term cohort study to 14 years of age of preterm infants treated with aminophylline showed an increase in the incidence of cerebral palsy (15), it remains to be determined that the CAP trial benefits persist to 5 years corrected age (21). Given the long-term cohort study to 14 years of age of preterm infants treated with aminophylline showed an increase in the incidence of cerebral palsy (15), it remains to be determined that the CAP trial benefits persist to 5 years corrected age (21).…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies of adenosine receptor activation or inhibition in hypoxic-ischaemic brain injury models have shown conflicting results from reduced to increased injury (14). A cohort study of theophylline in preterm babies born <1501 g birth weight examined at 14 years of age showed contrasting associations of increased rates of cerebral palsy and higher psychological test scores in those exposed to theophylline (15). Caffeine citrate at 10 mg ⁄ kg loading followed by 5 mg ⁄ kg ⁄ day was shown to increase energy expenditure, reduce weight gain and increase oxygen consumption in 9 preterm babies matched to 9 preterm babies not receiving caffeine (16).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, no randomised clinical trials with long term follow up assessing caffeine treatment have been reported. One recent cohort follow up study 22 provided conflicting evidence as to the potential effects of caffeine exposure. Davis et al 22 described an increase in cerebral palsy in those infants exposed to theophylline in the neonatal period, but also noted an increase in the mean intelligence quotient (IQ) in the same group of infants compared with controls not exposed to caffeine.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in contrast to those in the study of Davis et al, whose observational study showed an association between neonatal exposure to theophylline and cerebral palsy at 14 years of age in a cohort of VLBW children. 21 having a strong financial situation, and good home facilities. 22 The neurodevelopmental outcomes at 18 months in our study may not accurately predict neurological function later in childhood.…”
Section: Discussionmentioning
confidence: 99%